A Patient‐Centric Goal in Time to Blood Pressure Control from Drug Therapy Initiation. Issue 1 (14th January 2013) - Hong, Song Hee; Wang, Junling; Tak, Sunghee
Abstract A time frame in which newly diagnosed hypertensive patients attain blood pressure (BP) goal would guide patients through uncertainty associated with initiating drug therapy for hypertension control. This study estimates time to BP goal resulting from drug therapy initiation among real‐world hypertensive patients and identifies factors associated with variations in time to BP goal. The study uses a historical cohort design. Hypertensive patients who had initiated antihypertensive drug therapy between July 1, 2002, and December 31, 2003, were followed up to 12 months until the end of 2004. Electronic medical records from a medical group were linked with pharmacy claims, as well as with medical claims. Survival analyses were used to compare lengths of time needed to reach BP goals. A total of 223 patients from a real world practice setting had initiated antihypertensive drug therapy. The patients took 3.25 months (95% CI: 2.49–4.82) to reach BP goal. The patient‐centric time to BP goal was 7.1 weeks longer than those reported in controlled experimental settings. This finding highlights the gap between results of controlled clinical trials and their application to clinical practice, and informs healthcare practitioners of the importance of setting a patient‐centric goal in pharmacological treatment of hypertension. Clin Trans Sci 2012; Volume #: 1–6